Investigation of a Potential Pharmacokinetic Interaction Between Nebivolol and Fluvoxamine in Healthy Volunteers - Ana-Maria Gheldiu; Laurian Vlase; Adina Popa; Corina Briciu; Dana Muntean; Corina Bocsan; Anca Buzoianu; Marcela Achim; Ioan Tomuta; Ioana Todor; Maria Neag (Frontiers Media S.A., 2017)
Purpose: To investigate whether fluvoxamine coadministration can influence the pharmacokinetic properties of nebivolol and its active hydroxylated metabolite (4-OH-nebivolol) and to assess the consequences of this potential pharmacokinetic interaction upon nebivolol pharmacodynamics. Methods: This open-label, non-randomized, sequential clinical trial consisted of two periods: Period 1 (Reference), during which each volunteer received a single dose of 5 mg nebivolol and Period 2 (Test), when a combination of 5 mg nebivolol and 100 mg fluvoxamine was given to all subjects, after a 6-days pretreatment regimen with fluvoxamine (50-100 mg/day). Non-compartmental analysis was used to determine the pharmacokinetic parameters of nebivolol and its active metabolite. The pharmacodynamic parameters (blood pressure and heart rate) were assessed at rest after each nebivolol intake, during both study periods. Results: Fluvoxamine pretreatment increased Cmax and AUC0-∞  of nebivolol (Cmax: 1.67 ± 0.690  vs 2.20 ± 0.970  ng/mL; AUC0-∞: 12.1 ± 11.0  vs 19.3 ± 19.5  ng*h/mL ) and of its active metabolite (Cmax: 0.680  ± 0.220  vs 0.960 ± 0.290  ng/mL; AUC0-∞: 17.6 ±20.1  vs 25.5 ± 29.9  ng*h/mL). Apart from Cmax,AUC0-t and AUC0-∞, the other pharmacokinetic parameters (tmax, kel and t½) were not significantly different between study periods. As for the pharmacodynamic analysis, decreases in blood pressure and heart rate after nebivolol administration were similar with and without fluvoxamine concomitant intake. Conclusions: Due to enzymatic inhibition, fluvoxamine increases the exposure to nebivolol and its active hydroxylated metabolite in healthy volunteers. This did not influence the blood pressure and heart-rate lowering effects of the beta-blocker administered as single-dose. However, more detail studies involving actual patients are required to further investigate the clinical relevance of this drug interaction.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.